How Children Are Protected From COVID-19? A Historical, Clinical, and Pathophysiological Approach to Address COVID-19 Susceptibility - Massalska, Magdalena Anna; Gober, Hans-Jürgen (Frontiers in Immunology, 2021)
The origin and the global spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) in early 2020 was accompanied by high rates of mortality in regions belonging to the ancient silk road, such as the south of China, Iran, Turkey and the northern parts of Italy. However, children seem to be spared in the epidemic as very small percentage worldwide being ill. The protection of children and neonates suggests the involvement of a specific component of adaptive immunity present at early development. Native immunoglobulin belonging to the class of IgM is abundantly present in neonates and children and is known for its recognition of self- and altered self-antigens. Native IgM may be able to neutralize virus by the recognition of endogenous „danger signal” encoded in the viral envelope and originally imprinted in the membranes of infected and stressed cells. Noteworthy, thrombosis and vasculitis, two symptoms in severely affected adult and pediatric patients are shared between COVID-19 and patients with Behcet’s disease, an autoimmune disorder exhibiting a region-specific prevalence in countries of the former silk road. Molecular mechanisms and clinical indicators suggest reactive oxygen species as trigger factor for severe progression of COVID-19 and establish a link to the innate immune defense against bacteria. The selective pressure exerted by bacterial pathogens may have shaped the genetics of inhabitants at this ancient trade route in favor of bacterial defense, to the detriment of severe COVID-19 progression in the 21th century.